Effect of inhomogeneous distribution of non-metallic inclusions on crack path deflection in G42CrMo4 steel at different loading rates - S. Henschel; L. Krüger (Fracture and Structural Integrity)
An inhomogeneous distribution of non-metallic inclusions can result from the steel casting process. The aim of the present study was to investigate the damaging effect of an inhomogeneous distribution of nonmetallic inclusions on the crack extension behavior. To this end, the fracture toughness behavior in terms of quasi-static J-?a curves was determined at room temperature. Additionally, dynamic fracture mechanics tests in an instrumented Charpy impact-testing machine were performed. The fracture surface of fracture mechanics specimens was analyzed by means of scanning electron microscopy. It was shown that an inhomogeneous distribution significantly affected the path and, therefore, the plane of crack growth. Especially clusters of non-metallic inclusions with a size of up to 200 ?m exhibited a very low crack growth resistance. Due to the damaging effect of the clusters, the growing crack was strongly deflected towards the cluster. Furthermore, crack tip blunting was completely inhibited when inclusions were located at the fatigue precrack tip. Due to the large size of the non-metallic inclusion clusters, the height difference introduced by crack path deflection was significantly larger than the stretch zone height due to the crack tip blunting. However, the crack path deflection introduced by a cluster was not associated with a toughness increasing mechanism. The dynamic loading ( 1 0.5 5 s MPam 10 ? ? K? ) did not result in a transition from ductile fracture to brittle fracture. However, the crack growth resistance decreased with increased loading rate. This was attributed to the higher portion of relatively flat regions where the dimples were less distinct.